Cooperation among agricultural research libraries within the Agency for Agricultural Research and Development (AARD), and the role of the National Library for Agricultural Sciences (NLAS) as the coordinator development, problems and prospects - Mansjur, Surya (1985)
The purpose of this study is to describe the nature and extent of cooperative activities among agricultural research libraries within the AARD, and to identify the problems and factors that hinder or promote cooperation among these libraries.